University and airline bomber - Tošić-Malešević Nikola (Војно дело, 2016)
Since the second half of the 18th century (from the beginning of the industrial revolution) to date, the history of mankind has seen continuous vertiginous rise of science and technology. This has been the time of the greatest successes of the human race since its existence (the invention of numerous medicines for various diseases; creation and advance development of machines supporting the human work and recreation; building the spaceships; going to the Moon, etc.). However, this time period has also seen many unfavorable things (such as, creating machines to kill other people more easily; world wars; large-scale terrorist attacks; ruthless exploitation of human labor, etc.). All the above-mentioned led to that some groups of people and individuals considered this progress to be a threat to human species. Although to some extent they were right in their condemnations of these harmful things, some of these groups and individuals decided to oppose this progress by violent acts, which led to human casualties as well.